Effectiveness of Early Treatment with Steroids in Outcome of Sudden Sensorineural Hearing Loss. A study from Western Nepal - Rai, Shiwani; Koirala, Krishna; Sherpa, Pema (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Objective: To study the effect of early versus delayed treatment of Sudden Sensorineural Hearing Loss (SSNHL) in hearing outcome. Material and Methods: A retrospective study of patients with SSNHL was done from October 2012 to October 2014 to study the effect of early versus late treatment in hearing outcome in ENT department of Manipal Teaching Hospital, Pokhara, Nepal. Patients receiving treatment within 3 days of onset of symptoms were placed in early treatment group (ET) and those receiving treatment after 3 but within 7 days were placed in late treatment group (LT). Hearing outcome was assessed using pure tone average (PTA) and was carried out at presentation and then at 3,7,14 and 30 days after treatment. A mixed between and within- subject design ANOVA test was used to analyze the results using SPSS 20.0. Results: There were 29 patients in ET group and 25 patients in LT group. Mean age of the study population was 36.37 years (SD=7.868). The M:F ratio was 0.39:1. There was a significant interaction between time and treatment group, Wilk’s Lambda= 0.382, F (1.52, 79.196) = 19.83, p <0.001, partial eta squared =0.541. There was a substantial main effect of time, F (1.52, 79.196)= 180.36, p <0.001, partial eta squared = 0.776 suggesting significant improvement of hearing levels with time. The main effect comparing early and late treatment groups was also significant, F (1,52)= 5.799, p=0.02, partial eta squared = 0.100 suggesting significant difference in hearing levels in between the two treatment groups. Conclusion: Onset of treatment after the initial symptom significantly affects the outcome of hearing improvement in SSNHL. There are higher chances of improving if treatment is started within 3 days of onset of symptoms.